Land Transport Authority (LTA) and the transport management system in Singapore. - Chan, Debra Jin An. (2008)
This project evaluates the transport management system implemented by the LTA based on the objectives that it released in the White Paper (1996). It includes results from a survey conducted about the local transport system.